EVALUASI FAKTOR PENGARUH TINGKAT PELAYANAN JALAN SUNGAI RAYA DALAM KOTA PONTIANAK - Sukamto, -; Erwan, Komala; Mayuni, Siti (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2017)
River road segment in the highway is one of the main streets stronghold district highway, the airport traffic by road functions as a local road. The function of the local roads are public roads that function to serve local transportation with the characteristic travel a short distance, average speed is low, and the number of driveways is not restricted. The main objective of this study was to determine the level of service on the road river highway in order to give a solution would be to assist in improving the level of service. The method used in the analysis level of service on the river highway in 1997. The location is MKJI research conducted on roads in the river highway. The research activities carried out from 03 until December 9, 2016. The research data in the can at the time of the survey on this road is the traffic volume and speed of travel. While the survey side constraints and geomtri road starting from 15 July 2016-18 July 2016.waktu mileage vehicles, as well as the population of the river and city highway in Pontianak. From the analysis of the level of service roads in the river highway found the average level of service B is a steady flow, the speed is slightly limited by traffic, drivers can still freely in choosing speed. Keywords: Volume, Velocity, Capacity, splitters direction and density (density).